Relationships between Self-Efficacy and Teachers’ Well-Being in Middle School English Teachers: The Mediating Role of Teaching Satisfaction and Resilience - Wang, Xiaochen; Gao, Yang; Wang, Qikai; Zhang, Panpan (Behavioral sciences, 2024)
Teaching satisfaction and resilience play important roles in the education field, but most research focuses on higher education, with few scholars studying their impact on language teaching within the context of middle school education. In this sense, this study employs a mixed-methods research design, selecting 375 Chinese middle school English teachers to investigate the roles of teaching satisfaction and resilience in the relationship between self-efficacy and teachers’ well-being. A structural equation modeling approach and NVivo were utilized to analyze quantitative data and qualitative data, respectively. Quantitative results reveal that both teaching satisfaction and resilience mediate the relationship between self-efficacy and teachers’ well-being. Qualitative interviews reveal that teaching satisfaction primarily enhances job commitment, reduces job stress, improves student relationships, and increases professional growth. Meanwhile, resilience plays a crucial role in stress management, positive adaptation, and emotional regulation. This research offers insightful implications for improving teachers’ well-being and contributes significantly to the broader discourse on foreign language teacher education.